Robotic Ultrasound for Catheter Navigation in Endovascular Procedures - Langsch, Fernanda; Virga, Salvatore; Esteban, Javier; Gobl, Rudiger; Navab, Nassir (IEEE International Conference on Intelligent Robots and Systems, 2019)
Endovascular procedures require real time visual feedback on the location of inserted catheters. This is currently achieved using X-ray fluoroscopy, which causes exposure to radiation. This study describes an alternative method using a robotic ultrasound system for catheter tracking and navigation in endovascular interventions, focusing on endovascular aneurysm repair. This approach relies on the registration of pre-operative images to provide both a tracking trajectory and visual feedback of the real-time catheter position. The procedure was validated on healthy volunteers and on a phantom that included a realistic vessel structure, showing an average tracking error of the moving catheter tip of 1.78±1.02 mm.
CRIS-Team Scopus Importer:2023-03-08